The effectiveness of Near Infrared (NIR) filter in different weather conditions for night time surveillance applications - Nor Suhada Azid, 1989- author 638898; Mohd. Farid Mohd. Ariff, 1980- 513544; Fakulti Geoinformasi dan Harta Tanah 555724 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2013